Earnings quality of Taiwanese group firms - Yang Y.-J.; Kweh Q.L.; Lin R.-C. (2023)
This study examines the relationship between group firms and earnings quality. For the period 2000-2010, we examine the earnings quality of Taiwanese group and non-group firms through accrual persistence, earnings management, and conservatism. We show that group firms exhibit a lower quality of accrual persistence, have greater propensity to manage earnings, and are less conservative relative to non-group firms. Furthermore, we confirm the possible effects of group vertical relatedness and deviation of control rights from voting rights on earnings quality. These findings support the information asymmetry hypothesis that controlling shareholders have greater room to manage earnings in group firms. © 2014 City University of Hong Kong and National Taiwan University.